Rosen & Barkin's 5-minute emergency medicine consult - Schaider, Jeffrey (Philadelphia : Lippincott Williams & Wilkins, 2011)
"This best-selling emergency department reference is now in its thoroughly updated Fourth Edition. The foremost authorities provide practical information on over 600 clinical problems in a fast-access two-page outline format that's perfect for on-the-spot consultation during care in the emergency department. Coverage of each disorder includes clinical presentation, pre-hospital, diagnosis, treatment, disposition, and ICD-10 coding. Icons enable practitioners to quickly spot the information they need. This edition provides up-to-date information on topics such as emerging infections, new protocols, and new treatments"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Emergency medicine -- Handbooks, manuals, etc; Medical emergencies -- Handbooks, manuals, etc; Electronic books